2015
DOI: 10.1073/pnas.1509317112
|View full text |Cite
|
Sign up to set email alerts
|

RNA transcription modulates phase transition-driven nuclear body assembly

Abstract: Nuclear bodies are RNA and protein-rich, membraneless organelles that play important roles in gene regulation. The largest and most well-known nuclear body is the nucleolus, an organelle whose primary function in ribosome biogenesis makes it key for cell growth and size homeostasis. The nucleolus and other nuclear bodies behave like liquid-phase droplets and appear to condense from the nucleoplasm by concentration-dependent phase separation. However, nucleoli actively consume chemical energy, and it is unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
460
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(481 citation statements)
references
References 43 publications
20
460
1
Order By: Relevance
“…Phase transitions have recently been shown to mediate cytoplasmic organization at the subcellular level. The assembly and disassembly of nucleoli and other nuclear bodies cycle between liquid-phase droplets and solid-phase condensations and can be modulated by rRNA transcription (33). Phase transition of the microtubule-associated zinc finger protein plays an essential role in the assembly of the spindle apparatus and its associated components (34).…”
Section: Discussionmentioning
confidence: 99%
“…Phase transitions have recently been shown to mediate cytoplasmic organization at the subcellular level. The assembly and disassembly of nucleoli and other nuclear bodies cycle between liquid-phase droplets and solid-phase condensations and can be modulated by rRNA transcription (33). Phase transition of the microtubule-associated zinc finger protein plays an essential role in the assembly of the spindle apparatus and its associated components (34).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Furthermore, a mechanism has been proposed according to which this type of liquid-liquid phase separation involves unstructured domains in RNA-binding proteins. 16 The latter are referred to as low complexity domains or intrinsically disordered domains.…”
Section: Rna-driven Liquid-liquid Phase Separation During Nucleolus Fmentioning
confidence: 99%
“…In support of this view, recent in vitro work has shown the ability of fibrillarin to phase-separate at lower concentrations if yeast RNA was present. 10 It was also demonstrated that the RNA-binding domains and the GAR domain of NCL are important for its localization to the nucleolus. 33,34 This could mean that those domains are important for the protein to phase-separate in an RNA-dependent manner.…”
Section: Rna-driven Liquid-liquid Phase Separation During Nucleolus Fmentioning
confidence: 99%
See 1 more Smart Citation
“…These reversible droplets represent physiologically active protein or protein‐nucleic acid “bioreactors” (Hyman et al , 2014), which form through a process known as LLPS (Brangwynne et al , 2015). Such transient membrane‐less organelles have multiple cellular functions, such as p‐granule formation to establish intracellular gradients of RNA transcription (Brangwynne et al , 2009), the enrichment of RNA binding proteins in stress granules (Lin et al , 2015; Molliex et al , 2015), concentrating transcription factors in nucleoli (Berry et al , 2015), and the initiation of microtubule spindle formation (Jiang et al , 2015). However, the functional phase separation of nuclear proteins was shown to be disrupted by C9orf72 GR/PR dipeptide repeats (Lee et al , 2016) and is related to protein aggregation in neurodegeneration (Schmidt & Rohatgi, 2016).…”
Section: Introductionmentioning
confidence: 99%